Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2466142
|View full text |Cite
|
Sign up to set email alerts
|

Memorability of pre-designed and user-defined gesture sets

Abstract: We studied the memorability of free-form gesture sets for invoking actions. We compared three types of gesture sets: user-defined gesture sets, gesture sets designed by the authors, and random gesture sets in three studies with 33 participants in total. We found that user-defined gestures are easier to remember, both immediately after creation and on the next day (up to a 24% difference in recall rate compared to pre-designed gestures). We also discovered that the differences between gesture sets are mostly du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(105 citation statements)
references
References 34 publications
7
91
1
6
Order By: Relevance
“…Few studies have focused on understanding which gestures are guessable [27] and easy to memorize [21]. In their "guessability" experiment, Wobbrock et al [27] observed that user-defined gestures are easier to memorize than pre-defined gestures.…”
Section: Human and Gesture Executionmentioning
confidence: 99%
“…Few studies have focused on understanding which gestures are guessable [27] and easy to memorize [21]. In their "guessability" experiment, Wobbrock et al [27] observed that user-defined gestures are easier to memorize than pre-defined gestures.…”
Section: Human and Gesture Executionmentioning
confidence: 99%
“…During so, we may argue that the methods used in these studies are more statistical analyses than a proper reverse engineering of the human behaviors. Other studies focuses on finding newer methods of interaction or new gestures like Nacenta et al work [22], or by the introduction of different sensors for the human manipulation [14].…”
Section: The Search For the Best Gesture Interaction In Hcimentioning
confidence: 99%
“…Although the general interface is designed to take advantage of the multi-touch paradigm, during the design of the application we decided that-for some functions-menus, buttons, and sliders are preferable to invocation gestures that are sometimes difficult to discover and remember [36]. The following subsections describe the functionality of TC that goes beyond the individual transmogrifiers, and how it interacts with the wider computing context.…”
Section: The Transmogrification Canvasmentioning
confidence: 99%